Benthic communities and their drivers: A spatial analysis off the Antarctic Peninsula - Julian Gutt; Janina Arndt; Casper Kraan; Boris Dorschel; Michael Schröder; Astrid Bracher; Dieter Piepenburg (Limnology and Oceanography, 2019)
Multiple environmental factors control benthic community patterns, and their relative importance varies with spatial scale. Since this variation is difficult to evaluate quantitatively, extensive sampling across a broad range of spatial scales is required. Here, we present a first case study on Southern Ocean shelf benthos, in which mega‐epibenthic communities and biota‐environment relationships have been explored at multiple spatial scales. The analyses encompassed 20 seafloor, water‐column, and sea‐ice parameters, as well as abundances of 18 mega‐epibenthic taxa in a total of 2799 high‐resolution seabed images taken at 28 stations at 32–786 m depth off the northern Antarctic Peninsula. Based on a priori nesting of sampling stations into ecoregions, subregions, and habitats, analyses indicated most pronounced patchiness levels at finest (within transects among adjacent seabed photos) and largest (among ecoregions) spatial scale considered. Using an alternative approach, explicitly involving the spatial distances between the geo‐referenced data, Moran's Eigenvector mapping (MEM) classified the continuum of spatial scales into four categories: broad (> 60 km), meso (10–60 km), small (2–10 km), and fine ( 2 km. In contrast, few environmental variables contributed to explaining biotic structures at finer scales. These are likely rather determined by nonmeasured environmental variables, as well as biological traits and interactions that are assumed to be most effective at small spatial scales.